Prevalence of Blastocystis hominis in Patients with Type II Diabetes Mellitus in Kirkuk City, Iraq - Abeer Omer Ahmed; Abeer Abbas Ali; Hayder Jaleel Mardan (Medical Journal of Babylon)
Background: Blastocystis hominis is a prevalent human and animal bowel protozoan parasite, which is the most widespread eukaryotic organism in the human intestines. Intestinal parasite usually infects immunocompromised individuals; one of these is type II diabetic mellitus (TIIDM). Aim: The aim of the study was to assess the rate of infection with B. hominis in patients suffering from TIIDM. Materials and Methods: The current study is conducted on 50 participants (20 males and 30 females) (27 diabetic and 23 nondiabetic [control]), aged 25–75 years, diagnosed by a consultant physician, according to the laboratory diagnosis hemoglobin A1c (HbA1c), from November 2021 to March 2022. Two milliliters of venous blood was collected for the evaluation of the ratio of HbA1c with a sample of stool for the diagnosis of the presence or absence of B. hominis. Results: About the age, the highest age group in the TIIDM was 61–75 years, whereas in the control, the highest age group was 46–60 years. About education, 17 samples were from noneducated patients in the TIIDM group and 13 samples in the control group. About residence, 16 were rural residences in the TIIDM group and 23 urban samples in the control group. About autoimmune, 14 samples of diabetic patients infected with another autoimmune disease and 20 samples were not infected in the control group. About B. hominis, all diabetic patients were infected with B. hominis, but in the control group, just two persons have B. hominis infection. Conclusions: B. hominis was more common in the patients with diabetics than the controls. To better understand the relationship between possible risk factors and Blastocystis infection, the sample size must be increased, and the survey area must be expanded.